Pengaruh Adopsi Teknologi, Luas Lahan, dan Pendidikan Formal pada Petani Milenial di Kabupaten Brebes terhadap Ketahanan Pangan Rumah Tangga - Kiki Puspitasari; Irene Kartika Eka Wijayanti; Faizah Noviani (Yayasan Literasi Sains Indonesia, 2025)
This study aims to analyze the influence of agricultural technology adoption, land size, and formal education on household food security among millennial farmers in Brebes Regency. The impetus for this research arises from the significant role of younger generations as catalysts for agricultural transformation in the face of challenges such as land fragmentation, rice price volatility, and climate change, which jeopardize the stability of regional food security. This study employs a quantitative method with a survey approach involving 30 millennial rice farmers selected purposively. Primary data were collected through structured questionnaires and analyzed using multiple linear regression with the aid of SPSS software. The results show that simultaneously, agricultural technology adoption, land size, and formal education significantly affect household food security among millennial farmers, with an F-value of 9.634 and a significance level of 0.000 (<0.05). Partially, agricultural technology adoption and formal education have a positive and significant effect on food security, while land size has no significant effect. The coefficient of determination (R²) value of 0.526 indicates that these three variables explain 52.6% of the variation in household food security, while other factors may influence a larger portion of the variation. These findings emphasize that the food security of millennial farmers in Brebes Regency is more strongly determined by the level of technology adoption and formal education than by land size. Therefore, strategies to enhance food security should focus on agricultural modernization based on technology and the improvement of human resource capacity through education and training.